Molecular Species Delimitation and Morphometry in the Melampus bidentatus (Panpulmonata, Ellobiidae) Cryptic Species Complex - Inäbnit, Thomas; Tiedemann, Ralph; Dennis, Alice (Bulletin of the Society of Systematic Biologists, 2023)
The coffee bean snail Melampus bidentatus occurs in coastal salt marshes along the North American Atlantic and Gulf coasts, and the Caribbean. It was recently found that this large geographical span is actually occupied by a complex of three apparently cryptic species (preliminary called “North”, “South” and “Gulf”) with partially overlapping distributions. Until now it was not clear whether there are any morphological differences between the three species or which of the available names can be applied to which of the cryptic species. We used the already known distribution patterns of the cryptic species, as well as new barcode sequences to assign available names to the three cryptic species. We then compared morphological characters from 264 specimens using two approaches: an analyses based on 11 landmarks and another based on semi-landmarks of the entire shell outline. We were able to assign a nominal name to each of the three cryptic species: Melampus bidentatus for “North”, Melampus jaumei for “South” and Melampus gundlachi for “Gulf”. The morphometric analyses did not yield any diagnostic differentiating features; these cryptic species are hence diagnosible solely by genetic analysis, but may further phenotypically differ in some unseen internal features or in their physiology.